Integrasi Nilai Budaya dan Bahasa Keagamaan dalam Pengembangan Usaha Mikro Ramah Lingkungan - Umar Mukhtar Siregar; Hidayat Herman (Management Studies and Business journal, 2025)
This study examines the integration of cultural values and religious language in the development of environmentally friendly micro-enterprises. Environmental challenges and market pressures require business strategies that are not only technically sustainable but also culturally and morally legitimate. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and document analysis involving micro-entrepreneurs, religious leaders, and community figures. The findings indicate that cultural values shape production practices by emphasizing harmony with nature and limits on resource exploitation, while religious language frames business activities in moral terms such as trust, blessing, and prohibition of environmental harm. This integration influences three key dimensions of micro-enterprise development: sustainable production practices, moral legitimacy in business communication, and symbolic differentiation of products based on local and religious identity. However, market competition and limited access to capital and technology constrain the consistent application of these values in practice. The novelty of this study lies in its integrative analysis of cultural values and religious language as symbolic mechanisms that translate environmental ethics into business strategies. The findings contribute to interdisciplinary discussions on culture, religion, and green micro-enterprise development by demonstrating how meaning-making processes shape economic practices..